Conflitos ambientais, o direito à água e mediação no baixo São Francisco : a atuação do Ministério Público Federal em Sergipe - Barreto, Pablo Coutinho (2011)
This present study focuses on how the prosecutor faces environmental conflicts related to the fundamental water right. Its general purpose is to analyze the performance of the Federal Prosecutor in Sergipe in the mediation of environmental conflicts related to water down the San Francisco between the years 2004 and 2010. The specific objectives are threefold: i) examine the characteristics of the low water conflicts object facing San Francisco by federal prosecutors in Sergipe ii) specify the legal instruments used and operating strategy; iii) to investigate whether the actions of the Federal Prosecutor in the mediation of environmental conflicts is effective. We selected all sixteen cases in which federal prosecutors acted in the mediation of conflicts in water below San Francisco, between 2004 and 2010, and applied them on a sheet in order to collect and systematize information about the parties involved water in the conflict, the circumstances that led to the actions of the Federal Public Ministry, the type of environmental conflict established the legal measures taken to resolve such conflicts, and the result of the mediation process. After analyzing the data obtained, it was found that most environmental conflicts related to water rights refer to damage to the area of preservation and water pollution, the most relevant being those related to the restriction on multiple uses. The instruments most commonly used are the civil investigation and preparatory procedure, the request and notification, there is no record of the use of the term recommendation or adjustment of conduct. The strategy used by federal prosecutors in Sergipe has achieved effective results out of court swiftly, with a major reallocation of water disputes to the courts.